LINGUISTIC AND SCIENTIFIC ANALYSIS OF METHODS THAT INCREASE COMMUNICATIVE COMPETENCE IN TEACHING ENGLISH LANGUAGE (Proceedings of International Educators Conference, 2023)
Communicative competence really includes linguistic competence, as well as a set of facts that are part of socio-linguistic pragmatic competence, in an uncertain shape or form (rules and conventions of using language objects in context and other factors, such as relationships, etc.).Dell Hymes says that a language learner should have the following capabilities.